Pregnancy Outcome after Cerclage for Cervical Incompetence at a Private Hospital of Dhaka (Faridpur Medical College Journal, 2017)
Miscarriage, particularly recurrent mid-trimester miscarriage is a distressful condition. This form of miscarriage and preterm birth appear to have some etiologies. An important etiology is cervical incompetence that describes a disorder in which painless cervical dilatation leads to recurrent second trimester pregnancy losses. Every year more than 10 million preterm birth occurs and more than 1 million baby die from this common complication of pregnancy. The incidence of true cervical insufficiency is estimated at less than 1% of the obstetric population. In the index pregnancy, findings indicative of possible cervical insufficiency include cervical funneling, cervical shortening, and overt cervical dilatation. The main objective of the study was to explore the benefit from cervical cerclage in pregnant women with cervical incompetence. This is a retrospective observational study conducted over a period of twelve months. All cases delivered in Central Hospital were assisted by consultant obstetricians, in which 16(61.5%) out of 26 cases were delivered by caesarean section. Miscarriage rate was 11.53%. Out of the caesarean deliveries 2(12.5%) were at term and 14(87.5%) were at preterm. In this study 3(21.42%) babies born at 32nd and 33rd weeks, 6(42.85%) at 34th week and 2(14.28%) were at 35th week. There was no fetal loss. Extreme low birth weight was only one, 7(43.75%) of the babies had normal body weight for the area of study, 8 babies (50%) had low birth weight. The cervical cerclage procedure therefore should be available more widely to benefit those patients with proven or strongly suspected cervical incompetence.Faridpur Med. Coll. J. Jul 2017;12(2): 78-81